Modeling multirotor wake interference in quadrotor eVTOL flight dynamics and handling qualities - Wang, Yeping; Ji, Honglei; Lu, Linghai; Zhou, Pan (Elsevier, 2025)
This study presents a good-fidelity flight dynamics model for a quadrotor eVTOL aircraft, with a particular focus on the effects of multirotor aerodynamic interference on vehicle stability and handling qualities. A dynamic vortex tube model, enhanced to account for aircraft angular motions, is developed and integrated with dynamic inflow theory to compute rotor-induced and interference velocities efficiently. The model is validated against wind tunnel data and benchmark trim results, demonstrating strong predictive accuracy. Incorporating this interference model into a 6-DoF flight dynamics framework reveals that multirotor wake interference significantly modify both static and dynamic stability characteristics, especially in low-to-medium speed regimes. Moreover, aerodynamic interference degrades incidence stability, reduces pitch and heave damping, and adversely affects phugoid behavior. In the lateral-directional axes, it destabilizes the spiral mode and introduces non-monotonic variations in Dutch roll stability. Handling qualities analysis using ADS-33E-PRF metrics shows that interference reduces pitch bandwidth from Level 1 to Level 2 and marginally deteriorates pitch and roll dynamic stability, while improving pitch-axis quickness. These findings demonstrate that multirotor aerodynamic interference is not merely a performance issue but a critical factor influencing flight control design and certification. The proposed modeling approach offers a computationally efficient yet physically grounded method for assessing multirotor eVTOL handling qualities across the full flight envelope.
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 40 Engineering; 4001 Aerospace Engineering; Aerospace & Aeronautics; Quadrotor eVTOL; Aerodynamic interference; Handling qualities; Stability; Flight dynamics